An investigation of antibiofilm and cytotoxic property of MgO nanoparticles. (March 2019) - MubarakAli, D.; Manzoor, Muhammed A.P.; Sabarinathan, A.; Anchana Devi, C.; Rekha, P.D.; Thajuddin, N.; Lee, Sang-Yul
Abstract: MgO nanoparticles (MgONPs) have been widely used as antibacterial agents with the advantages of them being nontoxic and their unique biological properties. In this study, we synthesized MgONPs by co-precipitation method and characterized them by XRD, SEM and EDS analysis. The antibiofilm activity of MgONPs as observed quantitatively by crystal violet assay and their action on biofilm architecture were assessed in both Gram-positive and Gram negative uropathogenic bacteria. In addition, the cytotoxic effect of synthesized MgONPs was evaluated against human breast cancer, MCF-7 cells. The morphological changes of apoptosis were observed by Acridine Orange/Ethidium Bromide (AO/EB) staining using a fluorescent microscope. MgONPs inhibited more than 50% of the biofilms in most of the tested uropathogenic bacteria; notably 80% inhibition in the case of K. pneumoniae . MgONPs successfully inhibited the viability of MCF-7 cells at a concentration of 50 μg.mL −l . Given their antibiofilm properties; MgONPs could be used as a potential nanomaterial for in vivo applications such as coating for a medical implant. Graphical abstract: Image 1 Highlights: Magnesium oxide nanoparticles (MgONPs) synthesis and characterization. Reduction of the biofilm forming uropathogens upon treatment with MgONPs. MgONPs induce apoptosis in MCF-7 cell line. It can be used as a coating material for medical implants.